The synthetic antimicrobial peptide IKR18 displays anti-infectious properties in Galleria mellonella in vivo model - Ramalho, Suellen Rodrigues; de Cássia Orlandi Sardi, Janaina; Júnior, Edson Crusca [UNESP]; Marchetto, Reinaldo [UNESP]; Wender, Heberton; Vargas, Luiz Felipe Plaça; de Miranda, Antonio; Almeida, Claudiane Vilharroel; de Oliveira Almeida, Luís Henrique; de Oliveira, Caio Fernando Ramalho; Macedo, Maria Lígia Rodrigues (Elsevier, 2022)
Antimicrobial peptides (AMPs) are promising tools for developing new antibiotics. We described the design of IKR18, an AMP designed with the aid of computational tools. IKR18 showed antimicrobial activity against Gram-negative and Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). CD studies revealed that IKR18 assumes an alpha-helical structure in the membrane-mimetic environment. The action mechanism IKR18 involves damage to the bacteria membrane, as demonstrated by Sytox green uptake. Furthermore, IKR18 displayed synergic and additive effects in combination with antibiotics ciprofloxacin and vancomycin. The peptide showed anti-biofilm activity in concentration and efficiency compared with commercial antibiotics, involving the direct death of bacteria, as confirmed by scanning electron microscopy. The anti-infective activity of IKR18 was demonstrated in the Galleria mellonella model infected with S. aureus, MRSA, and Acinetobacter baumannii. The novel bioinspired peptide, IKR18, proved to be effective in the control of bacterial infection, opening opportunities for the development of further assays, including preclinical models.
Keywords: Anti-infective activity; Antibiofilm; Bacteria; Infection model; MRSA